Impact of Fixed Orthodontic Appliances on Blood Count and High-Sensitivity C-Reactive Protein Levels - Jiwanasha Manish Agrawal; Vidyesh Nadkerny; Anurag Tiwari; Mahesh Ghadage; Avantika Jadhav; Chetan Sharma; Dipooja Patil (Journal of Pharmacy and Bioallied Sciences)
Background: Fixed orthodontic appliances are widely used in dental practice to correct malocclusions and improving oral health. However, their impact on systemic inflammation and hematological parameters remains under-explored. Materials and Methods: A cohort of 60 patients, aged 12 –30 years, undergoing fixed orthodontic treatment, were enrolled in the study. Blood samples were collected at baseline, 1 month, and 6 months post-appliance placement. Hematological parameters, including white blood cell (WBC) count, red blood cell (RBC) count, hemoglobin levels, and hs-CRP levels, were measured using standard laboratory techniques. A statistical analysis was performed to determine significant changes over time. Results: At 1-month post-appliance placement, a significant increase in WBC count (mean increase of 12%) and hs-CRP levels (mean increase of 18%) was observed compared to baseline (P < 0.05). RBC count and hemoglobin levels remained relatively unchanged. By 6 months, WBC count and hs-CRP levels showed a decreasing trend, approaching baseline values, though hs-CRP levels remained slightly elevated (mean increase of 5% from baseline, P > 0.05). Conclusion: The use of fixed orthodontic appliances induces a transient inflammatory response, as evidenced by elevated WBC count and hs-CRP levels within the first month of treatment.